Election in Nepal: Security Management Strategy (Voice of Teacher, 2024)
The foundation of democracy is the election, and a free and fair election is a crucial component that helps to fortify democracy. For democracies like Nepal, they are more crucial. Elections must be viewed and handled as a process in a representative active democracy, not as a one-time occurrence that takes place on a specific day or over a constrained period of time. Political parties have the power and duty to address social and economic problems and build a prosperous nation since they are the primary force behind political and economic stability in Nepal. Elections at the federal, provincial, and local levels are held successfully and amicably. Controlling direct or indirect acts of violence that pose a serious threat to the integrity of the election process in order to influence election results is known as election security. In recent elections, Nepal has seen a rise in the number and types of electoral violence that have the potential to undermine democratic norms and interfere with free and fair elections. Using a qualitative research approach and a thorough analysis of secondary sources, the study aims to analyze Nepal's election security management in order to demonstrate election security in the previous elections in 2017 and 2022.